2019
DOI: 10.1016/j.jtho.2018.10.158
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in the Diagnosis and Treatment of Lung Cancer among People with Disabilities

Abstract: Introduction: Potential disparities in the diagnosis, treatment, and survival of patients with lung cancer with and without disabilities have rarely been investigated. Methods:We conducted a retrospective cohort study with a data set linking the Korean National Health Service database, disability registration data, and Korean Central Cancer Registry data. A total of 13,591 people with disabilities in whom lung cancer had been diagnosed and 43,809 age-and sex-matched control subjects in whom lung cancer had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 21 publications
(31 reference statements)
4
40
1
Order By: Relevance
“…We found that the stage of disease was more likely to be marked “unknown” among people with disabilities. Like a previous study on disparities in lung cancer ( 24 ), this trend was more evident in the severe disability group and among those with mental impairments. GC staging may be “unknown” because patients did not receive proper staging tests to establish an appropriate treatment plan, which means that they probably gave up subsequent treatment ( 35 ).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…We found that the stage of disease was more likely to be marked “unknown” among people with disabilities. Like a previous study on disparities in lung cancer ( 24 ), this trend was more evident in the severe disability group and among those with mental impairments. GC staging may be “unknown” because patients did not receive proper staging tests to establish an appropriate treatment plan, which means that they probably gave up subsequent treatment ( 35 ).…”
Section: Discussionsupporting
confidence: 66%
“…Our study showed that people with disabilities were more likely to receive no cancer treatment and were less likely to undergo surgery or chemotherapy, especially when their disability is severe. Our findings imply that people with disabilities may be discouraged from receiving cancer treatment by their healthcare providers or family members, who may undervalue the benefits of treatment and overemphasize complications in patients with disabilities ( 24 , 25 , 27 ). Furthermore, receiving less treatment was more evident in people with communication and mental impairments.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…1 Despite of its deadliest nature, early diagnosis and treatment can better the survival of the sufferer. 2 People from socio-economically backward section face the worst situation related to prognosis due to poor awareness, lack of accessibility to health services and costly treatment. They are often diagnosed at late stage resulting in poor survival and increased chance of disability.…”
Section: Introductionmentioning
confidence: 99%